Improving Energy Efficiency of Multi-Family Apartment Buildings Case of Jordan - Bataineh, Asma’ M.; Ali, Hikmat H. (International Journal of Energy Economics and Policy, 2021)
Saving energy is a high priority in developing countries and several energy-efficient initiatives are being introduced for that purpose. The residential sector is responsible for a big part of the world’s energy usage; most of this energy is used in heating, cooling, and artificial ventilation systems. The residential sector in Amman consumes more than 21% of the annual energy consumption, meanwhile multi-family residential apartments occupy more than 60% of that sector. With a view on developing energy-efficient structures, this study provides an overview of building design criteria that can reduce the energy demand for heating and cooling of multi-family apartment residential buildings. These criteria are based on the adoption of suitable parameters for the orientation of the building, shape, envelope system, use of insulation materials, passive heating and cooling mechanisms, setting of cooling and heating thermostat, lighting, and window’s ratio and glazing. This experiment measures the effect of these criteria on overall energy demand that reviewed and recommended the best design choices. This is beneficial for professionals in the design phase of energy-efficient multi-family residential buildings and decisions makers. The methodology that is used in the study was represented in field observation and surveys, besides, to use design-builder as a simulation tool to test the assumptions and the design strategies, the results indicate that a 6cm polystyrene insulated walls and roof for a north/west middle floor apartment and WWR ranges from 25 to 30% of double bronze glass will affect greatly in the energy demand. Keywords: energy-efficiency, multi-family residential apartment, design strategies JEL Classification: Q2 DOI: https://doi.org/10.32479/ijeep.11394